DEVELOPMENT OF REDUCTION REACTION LEARNING USING COMPUTER BASED LEARNING METHOD - Heri Sunandar; Soni Bahagia Sinaga (Jurnal Scientia, 2020)
Chemistry is the study of objects, their characteristics, structure, composition, and changes caused by interactions with other objects or chemical reactions. Chemistry is often referred to as the "central science" because it connects various other sciences, such as physics, nanotechnology, biology, pharmacy, medicine, bioinformatics, and geology. A reduction reaction is a chemical reaction that occurs in a redox reaction. The concept of the reduction reaction in redox reactions has undergone several stages of development. For this reason, it is necessary to prepare a learning media that can deliver subject matter that can attract the attention of students to study the material by implementing computer-assisted learning. It is hoped that it can make it easier to understand the reduction reaction material. Computer-Based Learning (CBL) is a computer for presenting learning material that aims to make students more active in learning material in the use of computer media. In its development, Computer Based Learning (CBL) has four learning system models, namely the tutorial model, practice and training models, simulation models, and instruction games models.